2009
DOI: 10.1002/ps.1697
|View full text |Cite
|
Sign up to set email alerts
|

Modified female calling behaviour in Cry1Ac‐resistant Helicoverpa armigera (Lepidoptera: Noctuidae)

Abstract: These results indicate that there is a fitness cost in terms of the female calling behaviour of the resistant strain. The lower proportion of females of the resistant strain showing calling behaviour could reduce the mating frequency of the resistant strain. The delayed onset time of calling in the resistant strain could reduce its mating time, and a reduction in the time spent calling could reduce the attractiveness of resistant females; this could also reduce the mating frequency of the resistant strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…The study of fitness costs associated with insect resistance to Bt insecticidal proteins is important for understanding resistance evolution and evaluating resistance management practices used to mitigate resistance to transgenic crops . Some studies on Bt ‐based fitness cost in H. armigera have been carried out before . However, this is the first report on the reproductive physiology associated with Cry1Ac resistance in H. armigera .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of fitness costs associated with insect resistance to Bt insecticidal proteins is important for understanding resistance evolution and evaluating resistance management practices used to mitigate resistance to transgenic crops . Some studies on Bt ‐based fitness cost in H. armigera have been carried out before . However, this is the first report on the reproductive physiology associated with Cry1Ac resistance in H. armigera .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that individuals with more vitellogenic follicles have larger egg production . We propose that factors affecting early life fitness have deleterious effects on fitness in later stages of development, as Bt ‐resistant individuals exhibit a delayed larval development, delayed calling behaviour and reduced mating behaviour . The significant decline in the number of eggs laid female −1 and the hatching rate in CK2 can be attributed to the low proportion of female calling behaviour during the first 3 days …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Cry1Ac-resistant strains of H. armigera showed significantly higher diapause rates than susceptible strains [22]. More recently, Zhao et al [23] observed altered calling behavior in the Cry1Ac-resistant strain of H. armigera. Compared with the susceptible strain, the resistant strain showed a reduced proportion of calling individuals, decreased rates of calling, different calling times, and a delayed calling peak.…”
Section: Resistance Selection and Fitness Costsmentioning
confidence: 94%